Identification of Circular RNAs Associated With Chemoresistance in Colorectal Cancer - Yao, Fei; Xiang, Xiaochen; Zhou, Chuanren; Huang, Qiyou; Huang, Xiaoying; Xie, Zhufu; Wang, Qiang; Wu, Qingming (Frontiers in Genetics, 2021)
Chemoresistance is a major clinical obstacle for the treatment of colorectal cancer (CRC). Circular RNAs (circRNAs) are a new type of non-coding RNA that participated in the development of chemoresistance. However, the profiles and effects of circRNAs in 5-fluorouracil and cisplatin-resistance of CRC are still unclear and need to be elucidated. In the present study, the profiles of circRNAs in CRC chemo-resistant (HCT8/5-Fu and HCT8/DDP) and chemo-sensitive (HCT8) cell lines were identified via RNA sequencing. In total, 48 and 90 differentially expressed (DE) circRNAs were detected in HCT8/5-Fu and HCT8/DDP cell lines, respectively. GO enrichment and KEGG pathway analysis were conducted of the host genes of DE-circRNAs, the results showed that the most significant enrichment pathways in HCT8/5-Fu and HCT8/DDP cell lines was base excision repair and Hippo signaling pathway, respectively. In addition, 11 common DE-circRNAs in the two drug-resistant cell lines (2 are up-regulated and 9 are down-regulated) were screened and verified by quantitative real-time PCR, hsacirc_023607 and hsacirc_007420 were found to be the circRNA with the highest up-regulation and down-regulation fold changes. However, functional studies showed hsacirc_023607 has no effect on CRC chemoresistance. Therefore, the regulatory networks of targeted miRNAs related to 5-fluorouracil or cisplatin-resistance were predicted and constructed, in which hsacirc_002482 was identified as a hub gene, and its overexpression could suppress HCT8/5-Fu and HCT8/DDP cell proliferation and promote cell apoptosis, and enhance cell chemosensitivity. Taken together, these results of the study suggested that hsacirc_002482 may play important roles in chemoresistance of CRC.